2017
DOI: 10.1002/mbo3.484
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of Bacillus thuringiensis strains from northwestern Himalayas toxic against Helicoverpa armigera

Abstract: In this study, we present the selection and the characterization of Bacillus thuringiensis (Bt) strains with respect to their cry/cyt gene content and toxicity evaluation toward one of the most important polyphagous lepidopteran pest, Helicoverpa armigera. Fifty‐six Bt isolates were obtained from 10 different regions of northwestern Himalayas, recording a total B. thuringiensis index of 0.62. Scanning electron microscopy revealed presence of bipyramidal, spherical, flat and irregular crystal shapes; SDS‐PAGE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
(64 reference statements)
3
8
0
Order By: Relevance
“…Similarly, Bt isolate RM11 expressed the toxicity on Plutella xylostella with 4.51 µg/ml[32]. Lone et al[41] reported two isolates, JK12 and JK17 with LC 50 value of 184.62 and 275.39 µg/ml against Helicoverpa armigera. Soares Figueiredo et al[42] found that synergistic effect of Vip3 and Cry1 proteins expressed more toxicity on S. frugiperda.…”
mentioning
confidence: 99%
“…Similarly, Bt isolate RM11 expressed the toxicity on Plutella xylostella with 4.51 µg/ml[32]. Lone et al[41] reported two isolates, JK12 and JK17 with LC 50 value of 184.62 and 275.39 µg/ml against Helicoverpa armigera. Soares Figueiredo et al[42] found that synergistic effect of Vip3 and Cry1 proteins expressed more toxicity on S. frugiperda.…”
mentioning
confidence: 99%
“… Lone et al (2017) reported that the toxic isolates have a remarkable use in the pest control. So, commercially abused to control insect pest and revealed the confirmed significance of innovative Bt .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Woldetenssay and Ashenafi (2008) isolated a total of 213 Bacillus-like colonies from 503 soil samples collected from the different agro-ecological zone of Ethiopia. Another study showed that about 89 Bacillus-like colonies were isolated from 207 soil samples of different sites (Lone et al 2017). Captivatingly, soil environment could be inhabited by diverse microbial community and preferred as the main source for Table 4 Bioassay evaluation of Bacillus thuringiensis against whitefly, Bemisia tabaci the isolation of Bacillus species in general and Bt in particular (Soares-da-Silva et al 2015).…”
Section: Discussionmentioning
confidence: 99%